USING THERMAL WALKS TO EXAMINE PEDESTRIANS' THERMAL (DIS)COMFORT WHEN TRANSITING ACROSS INDOOR, SEMI-OUTDOOR AND OUTDOOR THERMAL ENVIRONMENTS IN SINGAPORE'S EQUATORIAL CLIMATE - HENG SU LI (2021)
Master's